PERAN GREEN TRUST DALAM MEMEDIASI PENGARUH GREEN PERCEIVED VALUE TERHADAP GREEN PURCHASE BEHAVIOR - Surya Setiawan, I Putu Agus; Suryani, Alit (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 10 Nomor 1 Tahun 2016, 2016)
The purpose of this study is to analyze the effect of green perceived value on green purchase behavior and the role of green trust in mediating the relationship between the two variables. The population of this study was consumer of organic product in Denpasar City. The sampling method used was purposive sampling with 110 respondents. Analysis technique used was path analysis and Sobel Test. The results show that gren perceived value positively affect green purchase behavior and green trust was positively mediates the effects of green perceived value on green purchase behavior of organic products. It is recommended to the marketer of organic products to inform the comunity about the benefits of consuming organic products. additionally, farmer of organic products is expected to maintain the quality of their product.
Keywords: green perceived value, green purchase behavior, green trust